Exfiltration from sewers: effects of different types of leakage / Mohd Ashaari Ab Wahab ... [et al.] - Ab Wahab, Mohd Ashaari; Abdul Talib, Suhaimi; Baharom, Bahardin; Marwi, Mat Som (Institute of Research, Development and Commercialisation (IRDC), 2006)
This research was conducted to study exfiltration of wastewater from gravity sewers. Exfiltration through different types of sewer leaks were studied. With the different size of leakage areas and a constant thickness of soil bedding, it was found that the exfiltration rate reduces and became constant over a duration of one (1) to three (3) days. Knowing the exfiltration rate, the time taken for the polluted water exfiltrate from sewer pipes to reach the groundwater can be determined so that preventive measures can be taken to prevent it. From studies conducted, it can be shown that the size of the leakage area was found to play an important role in determining the size of the clogging zone, the increased in the clogging zone resulted in the decreased of exfiltration rate due to the accumulation of organic matters at the edge of the leakage area and trapped in the pores of the bedding soil.